2017
DOI: 10.1007/s00253-017-8350-1
|View full text |Cite
|
Sign up to set email alerts
|

Ketones 2-heptanone, 2-nonanone, and 2-undecanone inhibit DnaK-dependent refolding of heat-inactivated bacterial luciferases in Escherichia coli cells lacking small chaperon IbpB

Abstract: Many bacteria, fungi, and plants produce volatile organic compounds (VOCs) emitted to the environment. Bacterial VOCs play an important role in interactions between microorganisms and in bacterial-plant interactions. Here, we show that such VOCs as ketones 2-heptanone, 2-nonanone, and 2-undecanone inhibit the DnaKJE-ClpB bichaperone dependent refolding of heat-inactivated bacterial luciferases. The inhibitory activity of ketones had highest effect in Escherichia coli ibpB::kan cells lacking small chaperone Ibp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…These molecules freely pass also through biological membranes of target organisms and may elicit changes in plasma membrane potential depolarization and activate regulatory proteins [37]. VOCs can interact with and damage lipid membranes [38] and interact with hydrophobic segments in proteins [13,39]. In our study, we found for the first time that ketone 2-nonanone can act on bacterial cells through different targets and by different mechanisms.…”
Section: Three Genes (Synpcc7942_1362 Synpcc7942_0351 Synpcc7942_07mentioning
confidence: 56%
See 1 more Smart Citation
“…These molecules freely pass also through biological membranes of target organisms and may elicit changes in plasma membrane potential depolarization and activate regulatory proteins [37]. VOCs can interact with and damage lipid membranes [38] and interact with hydrophobic segments in proteins [13,39]. In our study, we found for the first time that ketone 2-nonanone can act on bacterial cells through different targets and by different mechanisms.…”
Section: Three Genes (Synpcc7942_1362 Synpcc7942_0351 Synpcc7942_07mentioning
confidence: 56%
“…It was demonstrated that ketones bind with protein (bovine serum albumin) [12]. Moreover, 2-nonanone and 2-undecanone demonstrated an inhibitory action on protein refolding in bacteria [13], which can suppress the expression of genes involved in Quorum Sensing regulation in bacterial cells [14] and negatively affected biofilm formation by Agrobacterium tumefaciens [15].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the volatiles of interest to us as potential Pa inhibitors (Table 3) have been noted previously among Pa volatiles, including 2-undecanone [57,[63][64][65][66][67]71,76], 2-heptanone [64][65][66][67]71,76], and methyl thiocyanate [67]. 2-heptanone has been noted to be an inhibitor of micro-organisms (bacteria) [78]. An important confounder in volatile studies, as also noted by others [63], is that uninoculated culture medium produces volatiles that could be confused with those of the micro-organisms of interest; in those of our four chromatographic studies described which required such controls, we have noted many of these, and whereas the media themselves, when exposed to Af, were not inhibitory, those volatiles were excluded from our group of candidates as Pa inhibitors.…”
Section: Discussionmentioning
confidence: 82%
“…Microbial volatiles are typically small lipophilic organic molecules [ 77 ]. The mechanism of inhibitory action of such volatiles has been ascribed to interactions with the hydrophobic segments of proteins [ 78 ]. Regarding our observations with the quorum-sensing mutants, that the lasR -/ rhlR - mutant was noninhibitory, the lasR- mutant was only somewhat inhibitory, and the rhlR- mutant was fully inhibitory, opens the possibility of now defining which downstream pathways in Pa are responsible for these differences.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that such VOCs as ketones 2-heptanone, 2-nonanone, and 2-undecanone effectively inhibit the DnaKJE-dependent refolding of heat-inactivated bacterial luciferases only in the E. coli ∆ibpB mutant strain lacking small chaperone IbpB [36]. Chaperone IbpB, which forms a complex with hydrophobic sites in proteins [37][38][39], appears to inhibit the complexation of these sites with hydrophobic ketones.…”
Section: Effect Of (−)-Limonene and (+)-α-Pinene On The Dnakje-dependent Refolding Of Heat-inactivated Bacterial Luciferasementioning
confidence: 99%